(untitled) (Acta Polytechnica CTU Proceedings, 2022)
Engine or battery powered two-wheeled vehicles are an essential part of a transport system. Its users are however more vulnerable in comparison with personal vehicles. In general, compared to four-wheel vehicles even a small percentage of accidents that include motorcycles causes a significant rate of all fatalities in the Czech Republic. Two-wheelers nowadays face the challenge of electric propulsion and wider user adoption. This fact emphasizes the need to assess rider´s behaviour. One way of examination of rider´s behaviour in safe and scientific environments is an interactive vehicle simulator. In order to develop a complex semi-active motorcycle simulator, a virtual model in Unity platform was created. The main purpose of this paper is to verify the longitudinal dynamics of the physical model for emerging interactive simulator. To achieve this goal, crucial parameters of the model were set. For validation of the model we defined several riding scenarios. Based on the data measured during a track test experiment in a real environment, model parameters further needed were indirectly defined. The results show that the output of the longitudinal dynamics model closely correlates with the real data gathered on a track.